Academic entrepreneurship in research universities: An organizational perspective - Yusof, Mohar (ASEAN Universities Consortium of Entrepreneurship Education (AUCEE), 2010)
The focus of this study is on academic entrepreneurship, an emerging area of inquiry in the last three decades. Specifically, this research evaluates, va1idates and tests an organizational, framework of academic entrepreneurship, and investigates the relationship between the identified organizational factors and academic entrepreneurship. The methodology used involves the collection and analysis of quantitative data and the implementation of this design is guided by the study's organizational, framework of academic entrepreneurship which adopts the corporate entrepreneurship view and measures academic entrepreneurship as an organization-level construct. The dependent variable in this research is academic entrepreneurship and the independent variables are structure, controls human resource management systems, culture and leadership behavior. Findings and results of the correlation and regression analyses, from this study will enable public research universities to evaluate the status of their entrepreneurial systems, and identfy enablers and barriers, for entrepreneurial development within their academic organizations.